A sugar biomarker proxy for assessing terrestrial versus aquatic sedimentary input - Hepp, Johannes; Rabus, Max; Anhäuser, Tobias (Organic geochemistry, 2016)
One of the most important and at the same time most challenging issues in paleolimnological research is the differentiation between terrestrial and aquatic sedimentary organic matter (OM). We therefore investigated the relative abundance of the sugars fucose (fuc), arabinose (ara) and xylose (xyl) from various terrestrial and aquatic plants, as well as from algal samples. Algae were characterized by a higher abundance of fucose than vascular plants. Our results and a compilation of data from the literature suggest that fuc/(ara+xyl) and (fuc+xyl)/ara ratios may serve as complementary proxies in paleolimnological studies for distinguishing between terrestrial and aquatic sedimentary OM.
Gesehen am 05.09.2019